An empirical analysis of electricity consumption intensity based on structure factor and efficiency factor. (6th June 2011) - Niu, Dongxiao; Gu, Zhihong
Energy, especially the electricity, is the basis of a country's economic development. It is of great significance for a country to develop the economy. Meanwhile, this also can illustrate the mechanism and change trend of electricity consumption. This paper regards the intensity of electricity consumption as the research object and uses it to study the quantitative relationship between electricity and economy. Mainly considering the structural factor and efficiency factor, this paper divided the change of electricity consumption intensity into structure share and efficiency share and put forward their calculating method, then used the statistical data from 1995 to 2007 of Beijing to calculate the structure share and efficiency share in the change of electricity consumption intensity and analysed the impact of economic structure adjustment and efficiency improvement on it. The result shows that the development of industrial structure and improvement of electricity utilisation efficiency are two major factors which could promote the decline of the electricity consumption intensity, based on it, some suggestions for making the industry's development plan and further study of the relationship between electricity and economy were given.